Influence of Anxiety Sensitivity and Negative Affect on Concussion Outcomes. Issue 5 (31st May 2022) - Caze, Todd; Williams, Kimberly; Boucher, Sarah; Price, August; Abt, John; Burkhart, Scott
Background: Approximately two million children sustain a concussion annually, with negative mood being associated with elevated initial symptom reporting and longer recoveries. Despite this finding, minimum research has explored the predictive value of a person's negative mood and propensity to misinterpret internal sensations (anxiety sensitivity) on concussion outcomes. Hypothesis/Purpose: The purpose of this study was to examine how the relationship between anxiety sensitivity, negative affect, and positive affect relate to various concussion outcomes. It was hypothesized that higher anxiety sensitivity, higher negative affect, and lower positive affect would be predictive of higher initial concussion symptom reporting, increased number of total visits, and longer time to medical clearance. Methods: Children aged 8-18 years who sustained a concussion were examined in an acute concussion clinic for diagnosis and treatment of injury. Patients were evaluated within 14 days of injury and remained under clinical care until cleared to return to activity/sport. Patients were administered the Anxiety Sensitivity Index-3 (ASI-3), The International Positive and Negative Affect-Short Form (I-PANAS-SF) and Post-Concussion Symptom Scale (PCSS). Independent t-tests were run for all independent variables. Linear regressions were run to determine potential predictive value of ASI-3 (cognitive, physical, social subscale and total score) and I-PANAS-SF (negative and positive affect) on concussion outcomes (initial visit concussion symptom scores calculated by PCSS, total number of clinical visits, and days till medically cleared). Results: A total of 43 children (age: 15.6±1.6 years) were enrolled. Independent t-tests for all independent variables resulted in females on average having higher ASI-3 subscale and total scores ( p <0.01). Sex was therefore entered as a control variable in the regression models. Higher negative affect was significantly predictive (β = 0.38, p =0.030) of higher initial visit concussion symptom reporting (R 2 =0.46, F(5, 36)=4.48, p =0.003). More days to clinic (β = 0.88, p ≤0.001) and higher ASI-3 physical subscale scores (β = 0.25, p =0.008) were predictive of more days until medical clearance (R 2 =0.88, F(5, 35)=5.33, p =0.001). Conclusion: Results from this study show that both a person's negative affect and anxiety sensitivity are not just related to concussion outcomes but also predictive. Negative affect and anxiety sensitivity are easy to measure and amenable to treatment. Targeted interventions on improving negative affect and normalizing symptoms to minimize misinterpretations (anxiety sensitivity), could improve concussion outcomes.